NILAI-NILAI PENDIDIKAN DAN PENGARUHNYA TERHADAP HUBUNGAN SOSIAL ANAK DALAM NOVEL TOTTO-CHAN KARYA TETSUKO KUROYANAGI - Nur Hastuti (Universitas Diponegoro, 2014)
chan by Tetsuko Kuroyanagi.The object research is Novel Madogiwa No Tottochan by Tetsuko Kuroyanagi that is published in 1981. This research has aim to get description of education values and the effects toward children social relationship in the novel of Totto-chan. The approach method to answer both problems is literary sociology approach. Litetature has relation with people in the society, the effort of people to addapt and change society. Sociology is objective and scientific study about human in society, study about institution and social process. The difference between literature and sociology is sociology does scientific and objective analysis. In other hand, literature infiltrates and penetrates social life and shows human ways to comprehend society with their feeling.The teaching result of education values and the effects for the children social relationship are:1. Want to listen what the students tell. We must respect each other and appreciate to the others. It happens when people is speaking to us, so we must pay attention and listen well. The social relationship with everyone created by communication can run well. 2. Give self confidence.When we give trust to the others to do their tasks, so we must believe that person can responsible for their task, so that that person can be success in their task. When we give believe to the other person to overcome their problem, so we have to be sure that they can do it well. The trust between one and others create harmonious social relationship. 3. Delete unpretentious feeling in disable children.Whoever our frien, we must love them eventhough they have lack (disable). Teacher Kobayashi also teach that children or students can not underestimate those disable person. This case makes children in Tomoe love each other, so that social relationship like friendship will create well without underestimate each other.